The Jamaica Reader : History, Culture, Politics - Smith, Matthew J. (Caribbean history scholar); Paton, Diana, 1969- (Book collections on Project MUSE., 2021)
"Combining more than one hundred classic and lesser-known texts, The Jamaica Reader presents a panoramic history of the country-from its pre-contact Indigenous origins to the present-to provide an unparalleled look at Jamaica's history, culture, and politics."--